The Implementation of Green Business in Coffee Shops to Support SDG 12 - Alvin Ferdiansyah; Usep Suhud (MJK PUBLISHER, 2025)
The increasing environmental impact caused by the coffee shop industry has raised the urgency for adopting sustainable business practices. This study aims to examine the implementation of green business practices in coffee shops as a strategy to support Sustainable Development Goal 12 (Responsible Consumption and Production). Using a qualitative-descriptive method based on secondary data analysis and literature review, this paper explores various sustainability initiatives including waste reduction, sustainable sourcing, energy and water efficiency, and consumer education. The findings reveal that adopting green business strategies not only helps reduce environmental footprints but also enhances customer loyalty, brand competitiveness, and operational efficiency. However, challenges such as high initial investment costs, limited sustainable supply chains, and low consumer awareness remain significant obstacles. To overcome these challenges, the study suggests strategic collaborations with communities and governments, offering incentives to eco-conscious customers, and utilizing digital technologies to optimize sustainability efforts. This study contributes to enriching insights into how coffee shops can create added value while achieving environmental, economic, and social benefits simultaneously.